Self employment among Italian female graduates - Francesco Chelli; Luisa Rosti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2009)
Purpose: To investigate the gender impact of tertiary education on the probability of entering and remaining in self employment. Design/methodology/approach: We exploit a data set on labour market flows produced by the Italian National Statistical Office by interviewing about 62,000 graduate and non graduate individuals in transition between five labour market states: Dependent workers; Self-Employed workers; Unemployed persons; Non active persons. From these data we constructed an average ten-year transition matrix (1993-2003) and investigated the flows between labour market conditions by applying Markovian analysis. Findings: Our data show that education significantly increases the probability of entering self employment for both male and female graduates, but it also significantly increases the transition from self employment to dependent employment for female graduates, thereby increasing the percentage of female graduates in paid employment and reducing the percentage of women in entrepreneurial activities. We argue that the disappointment provoked by the gender wage gap in paid employment may induce some female graduates with low entrepreneurial ability to set up on their own, but once in self employment they have lower survival rates than both men in self employment and women in paid employment. Thus, what we observe overall, is that education widens the gender gap between self employed workers and employees for individuals persisting in the same working condition. Originality/value: Our data enable us to shift the focus of the relationship between education and entrepreneurship from the probability of being self employed to the probability of entering and surviving in this condition.
Keywords: 330